The Network Approach to Major Depressive Disorder: A Critical Realist Perspective - Johnson, Lennox (New Zealand Sociology, 2023)
Lack of progress in treating major depressive disorder (MDD) along with critiques of the reductionist biomedical model have motivated psychiatric researchers to develop alternative models of mental disorders. Over the last decade, network models have been developed that conceptualise mental disorders as the product of dynamic causal interactions between psychiatric symptoms, especially when these symptoms form self-reinforcing feedback loops. This article discusses how problems with the biomedical model have motivated research into network models of MDD. The network approach is then compared with critical realist (CR) theorising on MDD within the sociology of mental health. This article argues that critical realism and network approaches overlap significantly in their ontological and epistemological assumptions about mental disorders. Therefore, CR and network models are potentially complementary approaches for sociological theorising about MDD. The final section of this article discusses tensions between these two approaches and limitations of current network models of MDD from a CR perspective.